The Soil Microbiomes of American Ginseng (Panax quinquefolius) Cultivated in North America Differ by Location but Not Always by Disease Status - Isabella J. Maggard; Kayla B. Deel; Ying Gao; A. Bruce Cahoon (PhytoFrontiers)
One of the greatest challenges faced by ginseng producers is control of fungal pathogens that adversely affect harvest yields and are a contributing factor to replant failure syndrome. The goal of this project was to survey the soil microbiome of healthy versus diseased American ginseng grown in North America. Soils associated with healthy and diseased plants were collected from commercial farms in Garett County, Maryland, and Marathon County, Wisconsin. Environmental DNA metabarcoding was used to compare the bacterial and fungal microbiomes of healthy versus diseased plants from both locations. The most common bacteria occurred within the phylum Proteobacteria, Firmicutes, and Bacteroidota and the most common fungi occurred within Ascomycota, Basidiomycota, Mortierellomycota, and Glomeromycota. Overall, alpha- and beta-diversities were statistically significant between the two locations. Community analyses (beta-diversity) of the Maryland site revealed a significant difference in the bacterial composition of soils associated with healthy versus diseased plants but not in the fungi. Conversely, there was a significantly different assemblage of fungi in healthy versus diseased associated soils from the Wisconsin site, but not for bacteria. Our results, when compared to previous metabarcoding studies, suggest that there is little congruence between the soil microbiomes associated with cultivated ginseng and that we are still in the early stages of ginseng soil rhizosphere exploration. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.